Sosio-Eco- Religio -Culture dalam Penyelamatan Krisis Lingkungan Hidup - Husni Thamrin (Universitas Riau, 2018)
One of the ironies of the development of human civilization is the development and modernization is intended to improve the quality of human life, but it is more often the presence of people become victims of development and modernization. More ironically, land and indigenous peoples are victims of an anthropocentric perspective and government policies that do not favor the local community.This is attributable to several factors: First, the ideology of developmentalism does not incorporate local wisdom, especially regarding indigenous land policy and management and wealth preservation socio-eco-religio-cultural as an integral part of all development programs. In the ideology of developmentalism traditionalism is the opposite of modernization so that all that is traditional, including indigenous lands rich culture and local wisdom considered adaptive in the times. Second, misperceptions people who think the indigenous people of Malays as a destroyer of the environment that must be removed or relocated in order to save the environment. Yet, precisely Malays indigenous peoples are the guardians of the environment from the invasion and destruction by outside communities, immigrant communities. Third, the nature only in terms of economic value, so that the release of the entire ecological value, the local political, social, cultural, spiritual and moral associated with customary land and the lives of indigenous peoples in the surrounding. Exploit indigenous lands and natural resources for the purpose of economic development and seen off as not have negative consequences for the existence of the indigenous population. Fourth, modernization and progress of civilization seen and measured primarily by the quality of the physical-economic-capitalistic. To improve the socio-economic level of local communities, especially the Malays must be returned to the ethical values of indigenous peoples. Socio-economic rights of indigenous peoples should be recognized and guaranteed by the government. There must be political commitment at global and national levels to protect the land rights of indigenous peoples and all the wisdom of socioeconomic Through paradigm approach socio-eco-religo culture is to save the existence of indigenous land as a factor supporting economic activity and all the wealth and wisdom of traditional, it can also be save the ecological crisis is mainly caused by faulty worldview that policy makers anthropocentric-capitalistic paradigm should be changed to sosio-eco-religio culture perspective.